Water with reduced intermolecular forces

A measurement box controls temperature and humidity to accurately measure water evaporation rates, addressing the complexity and cost of existing methods, thereby assessing magnetic treatment's effectiveness and promoting water quality and biological activity.

JP7661649B2Active Publication Date: 2025-04-15DENDO INDUSTRY CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022212932
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-04-15
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

Existing methods for evaluating the effect of magnetic treatment on water molecules are complex and expensive, lacking a simple and cost-effective way to confirm the change in intermolecular forces, which affects the quality and biological activity of treated water.

Method used

A measurement box is devised to control temperature and humidity, allowing accurate measurement of the evaporation rate of water, which reflects the change in intermolecular forces, thereby evaluating the effectiveness of magnetic treatment.

Benefits of technology

The evaporation rate method provides a simpler and more reliable assessment of magnetic treatment's impact on water, enhancing the control of water quality and promoting biological activity, such as increased plant growth and reduced mold formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661649000001
    Figure 0007661649000001
  • Figure 0007661649000002
    Figure 0007661649000002
  • Figure 0007661649000003
    Figure 0007661649000003
Patent Text Reader

Abstract

To provide water with reduced intermolecular force.SOLUTION: The present invention provides water or natural water in which an evaporation rate at room temperature is enhanced through magnetic treatment by 10% or more or to 0.01 millimeters per hour or more, compared to the evaporation rate before the magnetic treatment, measured under the same conditions.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention uses the change in the binding force between water molecules caused by magnetic treatment in a manner similar to that of the conventional oxygen isotope method. 17 The present invention relates to the discovery of a method for evaluating water that is simpler, less expensive, and more reliable than a method for measuring the half-width of the nuclear magnetic resonance spectrum of O. In addition, the present invention relates to the discovery, in the course of evaluating various magnetically treated waters using the evaluation method of the present invention, that it is possible to produce water that exhibits biological activity (for example, promotes plant growth) by suppressing the binding strength of the water to a lower level compared to water before the treatment, even after several months have passed since the date of magnetic treatment. [Background technology]

[0002] Magnetic treatment has been used as a means of imparting biological activity to water and natural water. Various magnetic treatment devices have been devised, including a simple device in which water is passed through a water pipe sandwiched between the north and south poles of a magnet of several thousand to tens of thousands of gauss (Non-Patent Document 1), and a large-scale circulation type device (Non-Patent Document 2). However, there are few methods for evaluating the change in the binding force between water molecules due to magnetic treatment. 17 O-NMR method (oxygen isotopes 17 However, only a method for measuring the half-width of the nuclear magnetic resonance spectrum of O has been reported (Non-Patent Documents 1 and 2), and therefore a simpler and less expensive method for confirming the effect of the magnetic treatment has been desired. [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] Satoshi Kiki, Kenzo Kudo, Tatsuya Fukasawa, Tatsuo Shimizu, Fundamental Study on the Effect of Magnetic Treatment of Water. Proceedings of the Symposium on Sanitary Engineering, Vol. 11, pp. 123-126, 2003. [Non-Patent Document 2] Sumio Masuda, Katsumi Ishikawa, Kimiko Tanabe, Tetsuya Kusuda, Masanori Ishiguro, A study on magnetic treatment of wastewater. Environmental Technology, Vol. 21, No. 2, pp. 103-106, 1992. Summary of the Invention [Problem to be solved by the invention]

[0004] Water 17 O-NMR method was used to measure oxygen isotopes. 17 When the nuclear magnetic resonance spectrum of O becomes sharp (the half-width becomes smaller), this is understood to indicate that some of the hydrogen bonds between water molecules are broken, the size of the aggregates (clusters) formed by the hydrogen bonds of water molecules becomes smaller, and the movement of water molecules becomes more active (Non-Patent Documents 1 and 2). In other words, in water that has been sufficiently magnetically treated, the hydrogen bonds between molecules are weakened. If the intermolecular forces of water are weakened, the evaporation rate of water will be increased. Therefore, if a simple and inexpensive measuring device that can accurately measure the evaporation rate of water can be invented, it would be possible to eliminate expensive, complicated, and less versatile methods. 17 This will enable the effectiveness of magnetic treatment to be confirmed as an alternative to O-NMR methods, making it easier to control the quality of magnetically treated water. [Means for solving the problem]

[0005] If we look at the change in water vapor pressure during the evaporation process of water, we see that at the water surface it is at the saturated water vapor pressure for the temperature at that time (water and water vapor are always in equilibrium). On the other hand, at a location far enough away from the water surface, the water vapor pressure drops to the humidity of the measurement environment at that time. In other words, the evaporation of water is driven by this concentration difference of water molecules. This movement of molecules due to concentration differences can be considered a diffusion phenomenon and can be expressed by the following equation. Evaporation rate = (diffusion coefficient) × (saturated water vapor pressure - humidity of measurement environment) ÷ (travel distance) (1) In order to accurately compare the evaporation rates between samples, it is necessary to prepare a measurement environment in which the travel distance can be strictly matched. The travel distance specifically refers to the distance that the evaporated water molecules travel until they meet the air flow in the laboratory. Since a normal petri dish is only about 1 cm deep, in a simple evaporation experiment in which water is poured into the dish and the change in the water level on the liquid surface is observed, the air flow in the laboratory may directly reach the liquid surface, making the travel distance unstable, making it impossible to evaluate the difference in evaporation rate between samples with good reproducibility. On the other hand, in order to match the measurement temperature and humidity environment between samples, the petri dishes containing the sample water must be placed together in the laboratory as much as possible. Therefore, we devised a measurement box with an open top to collect the sample water in a specific place in a laboratory where the temperature and humidity are controlled, and confirmed that the evaporation rate between samples can be accurately measured by measuring the time change in the weight of each sample water in the measurement box, which led to the present invention. The depth of the devised measurement box corresponds to the travel distance in equation (1). This length should preferably be at least 30 centimetres, and the working space at the bottom of the box should preferably be no more than 0.2 square metres. Effect of the Invention

[0006] The effect of magnetic treatment on water 17 O-NMR method (oxygen isotopes 17The method of evaluating the change in the intermolecular force of magnetically treated water from the degree of decrease in the half-width of the nuclear magnetic resonance spectrum of O) was an expensive evaluation method that could not be said to be simple, but instead, in the present invention, it is possible to evaluate the change in the intermolecular force of magnetically treated water from a simple evaluation of the evaporation rate of water, which makes it easier to control the quality of the magnetically treated water (Example 1). In addition, when two types of natural water with significantly different evaporation rates described in Example 1 were dropped onto a Teflon sheet surface and the contact angle formed by the droplets was measured, no significant difference was observed (Comparative Example 1 and Comparative Example 2). It can be seen that the measurement of the evaporation rate is more effective than the measurement of the contact angle as a method for evaluating the change in the intermolecular force of water due to magnetic treatment. Furthermore, while evaluating various magnetically treated waters, it was confirmed that it was possible to produce water with a significantly higher evaporation rate than the water before treatment over a period of several months (see Example 2 and FIG. 2).

[0007] When the evaporation rate of natural water is increased by magnetic treatment to preferably 35% or more, or 0.01 mm / hour or more, compared to untreated natural water, when the magnetically treated natural water is used to grow a plant, as is clear from a comparison of the results of Example 3 and Comparative Example 3, the yield is increased when the magnetically treated water is used, and as is clear from a comparison of Figures 3 and 4, the ratio of edible parts to the total length of the plant is increased by using the magnetically treated water, or conversely, the roots can be shortened. Furthermore, in the case of a growth test using magnetically treated natural water as described in Example 4, no mold was observed even in an environment where humidity tends to be high in a dark place, but in the case of a growth test using non-magnetically treated natural water, when the plant was stored in a dark place in the same manner, obvious mold was observed on the 9th day after the start of the growth test, as described in Comparative Example 4.

[0008] The electrical conductivity of natural water used to produce magnetic water that exhibits biological activity such as promoting plant growth is preferably 100 microsiemens per centimeter (μS / cm) or less at 25 to 28°C, and most preferably 70 microsiemens per centimeter (μS / cm) or less.

[0009] In order to confirm the state between adjacent water molecules in the natural water that was effective for plant growth described in Example 3, the magnetically treated natural water was once frozen, and the heat of fusion of the ice produced during the heating process was measured using a differential scanning calorimeter as described in Example 5. The heat of fusion was 283 joules per gram. On the other hand, as described in Comparative Example 5, the heat of fusion of natural water that was not magnetically treated was similarly measured and was 330 joules per gram. The large decrease in the heat of fusion due to magnetic treatment can be understood to indicate that the intermolecular force of water that forms ice has decreased. Therefore, the results of Example 1 and Example 5 show that the decrease in the intermolecular force of adjacent water molecules due to magnetic treatment can be evaluated by mutually independent measurement methods. [Brief description of the drawings]

[0010] [Figure 1] This figure shows the change in the weight of the residual water in each of two petri dishes placed in a measurement box over time from the start of the evaporation test, for one petri dish into which untreated natural water (electrical conductivity, 28°C, approximately 60 microsiemens per centimeter (μS / cm)) was poured, and one into which the natural water had been magnetically treated and which had been left for 42 days between the date of magnetic treatment and the date of measurement. (Example 1) [Diagram 2] This is a diagram showing how the increase in the water evaporation rate due to magnetic treatment (the effect of magnetic treatment) decreases with the number of days elapsed since the production date of the magnetically treated natural water, when untreated natural water (electrical conductivity, 28°C, approximately 60 microsiemens per centimeter (μS / cm)) is magnetically treated (Example 2). [Diagram 3] For untreated natural water (electrical conductivity, 28°C, approximately 60 microsiemens per centimeter (μS / cm)), magnetic treatment was performed under the same conditions as the magnetic treatment used in Example 1, and arugula sprout growth tests were performed for 10 days from May 4, 2022 using only natural water that had been magnetically treated for 41 days. This is a diagram showing the appearance of the resulting arugula sprout seedlings. (Example 3) [Figure 4]A growth test of arugula sprouts was conducted for 10 days from May 4, 2022 using only untreated natural water (electrical conductivity, 28 ° C., approximately 60 microsiemens per centimeter (μS / cm)). This is a diagram showing the appearance of the resulting arugula sprout seedlings. (Comparative Example 3) [Diagram 5] The untreated natural water used in Example 1 (electrical conductivity, 28°C, approximately 60 microsiemens per centimeter (μS / cm)) was subjected to magnetic treatment under the same conditions as in Example 1 for 42 days, and the amount of heat generated by crystal formation during the freezing process (temperature drop rate of 5°C per minute) and the amount of heat absorbed by ice melting during the heating process (temperature rise rate of 5°C per minute) were measured using a differential scanning calorimeter, and this shows the heat generation and endothermic curves observed during each process. Freezing and melting were repeated twice in this measurement. [Figure 6] The amount of heat generated by crystal formation during the freezing process (temperature drop rate of 5°C per minute) and the amount of heat absorbed by ice melting during the heating process (temperature rise rate of 5°C per minute) were measured using a differential scanning calorimeter for the untreated natural water (electrical conductivity, 28°C, approximately 60 microsiemens per centimeter (μS / cm)) used in Example 1, and this shows the heat generation / endothermic curves observed during each process. In this measurement, freezing and melting were repeated twice. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES

[0011] The measurement box was set in a laboratory with a room temperature of 28°C and a relative humidity of 55%. Two petri dishes (inner diameter 87 mm) for pouring the sample water and an upper-pan electronic balance were placed in the box. 25.6 grams of untreated natural water (electrical conductivity, 28°C, approximately 60 microsiemens per centimeter (μS / cm)) and natural water that had been magnetically treated for 42 days were poured into each petri dish, and the weight loss of the remaining water in the petri dish due to the water evaporating from the water surface of the petri dish with the top open was measured, and the results shown in Figure 1 were obtained. It is clear that the weight loss of the magnetically treated natural water is faster than that of the magnetically treated natural water with respect to the elapsed time, as the slope of the graph is steeper. The slope of each graph corresponds to the evaporation rate, and the evaporation rate was calculated from the slope, resulting in a loss rate of 0.265 grams per hour for the untreated natural water and 0.342 grams per hour for the magnetically treated natural water. The drop in the water level per hour was calculated from the area of ​​the petri dish opening and the density of the water at the measured temperature, resulting in 0.0447 mm for untreated natural water and 0.0578 mm for magnetically treated natural water.

[0012] The untreated natural water used in Example 1 (electrical conductivity: 28°C, approximately 60 microsiemens per centimeter (μS / cm)) was stored for a sufficiently long time in a laboratory at 25°C, and then dropped onto a Teflon sheet in the laboratory. The contact angle formed by the droplet with the sheet surface was measured using the θ / 2 method. The average value of five measurements was 117.4 degrees, with a standard deviation of 0.49. Comparative Example 2

[0013] The untreated natural water used in Example 1 (electrical conductivity: 28°C, approximately 60 microsiemens per centimeter (μS / cm)) was magnetically treated under the same conditions as those used in Example 1, and 43 days had passed before the measurement date. The natural water was then stored for a sufficiently long time in a laboratory at 25°C, after which it was dropped onto a Teflon sheet in the laboratory, and the contact angle formed by the droplet with the sheet surface was determined using the θ / 2 method. The average value of five measurements was 117.0 degrees, with a standard deviation of 0.63. Example 2

[0014] The untreated natural water used in Example 1 (electrical conductivity, 28°C, approximately 60 microsiemens per centimeter (μS / cm)) was subjected to magnetic treatment under the same conditions as those used in Example 1, and the change in the evaporation rate of the magnetically treated natural water with the increase in the number of days since the date of production was measured using the measurement box described in Example 1 (experimental room temperature 27.5°C, laboratory relative humidity 57%), obtaining the results shown in Figure 2. Natural water was produced in which the evaporation rate was significantly higher over a period of several months than before treatment. Example 3

[0015] For the untreated natural water used in Example 1 (electrical conductivity, 28°C, approximately 60 microsiemens per centimeter (μS / cm)), a growth test of arugula sprouts was conducted for 10 days from May 4, 2022, using only natural water that had been magnetically treated under the same conditions as the magnetic treatment used in Example 1 and had been left for 41 days, and the results shown in Figure 3 were obtained. The harvest yield was 2.0 grams. For the growth test, paper towels were laid in a petri dish, and arugula sprout seeds (total amount 1.5 grams) were evenly placed on top of the paper towels. The magnetically treated natural water was appropriately dropped into the petri dish so that the surface of the seeds did not dry out. The growth test was completed in a dark place for the first 6 days and with a cultivation LED light turned on 24 hours a day for the remaining days. Comparative Example 3

[0016] Using only the untreated natural water used in Example 1 (electrical conductivity, 28 ° C., approximately 60 microsiemens per centimeter (μS / cm)), a growth test of arugula sprouts was conducted for 10 days from May 4, 2022, and the results shown in FIG. 4 were obtained. The harvest yield was 1.9 grams. The growth test was performed by laying a paper towel in a petri dish, evenly placing arugula sprout seeds (total amount 1.5 grams) on top of it, and dropping the natural water into the petri dish as appropriate so that the surface of the seeds does not dry out. The growth test was completed by keeping the seeds in a dark place for the first 6 days and turning on the cultivation LED light for 24 hours on the remaining days. Example 4

[0017] For the untreated natural water used in Example 1 (electrical conductivity, 28°C, approximately 60 microsiemens per centimeter (μS / cm)), a growth test of arugula sprouts was started on May 4, 2022, using only natural water that had been magnetically treated under the same conditions as the magnetic treatment used in Example 1 for 41 days. The growth test was carried out by laying a paper towel in a petri dish, evenly placing arugula sprout seeds (total weight 1.5 grams) on top, dropping the magnetically treated natural water into the petri dish as needed to prevent the surface of the seeds from drying, and starting the growth test in a dark place. No mold was observed on the medium during the 6-day growth period in the dark. Comparative Example 4

[0018] Using only the untreated natural water used in Example 1 (electrical conductivity, 28 ° C., approximately 60 microsiemens per centimeter (μS / cm)), a growth test of arugula sprouts was started on May 4, 2022. The growth test was carried out by laying a paper towel in a petri dish, evenly placing arugula sprout seeds (total amount 1.5 grams) on top of it, dropping the natural water into the petri dish as appropriate so that the surface of the seeds does not dry out, and starting the growth test in a dark place. On the sixth day of growth in the dark, obvious mold colonies were confirmed on the medium due to the remnants of the seed coat and the decay of ungerminated seeds. Example 5

[0019] The untreated natural water used in Example 1 (electrical conductivity, 28°C, approximately 60 microsiemens per centimeter (μS / cm)) was magnetically treated under the same conditions as in Example 1 for 42 days, and the heat of fusion during the heating and melting process after freezing was measured using a differential scanning calorimeter. The results are shown in Figure 5. 9.890 milligrams of the magnetically treated natural water was sealed in an aluminum sealed pan, cooled to -40°C at a temperature drop rate of 5°C per minute, and held for 1 minute to freeze the magnetically treated natural water. Next, the magnetically treated natural water was heated to 25°C at a temperature rise rate of 5°C per minute, and the heat of fusion due to the melting of ice in the magnetically treated natural water during the heating process was measured using a differential scanning calorimeter. The magnetically treated natural water was then cooled again to -40°C at a rate of 5°C per minute and held for 1 minute to refreeze, and subsequently heated to 25°C at a rate of 5°C per minute, and the heat of fusion due to the remelting of the ice in the magnetically treated natural water during the heating process was measured again using a differential scanning calorimeter. The endothermic curves observed from the two meltings of ice in the magnetically treated natural water were almost completely in agreement with each other, and the heat of fusion was 283 joules per gram (J / g). In the evaluation of the heat of fusion, the heat of fusion of ice in ultrapure water measured in a similar manner was set to 333 joules per gram (J / g), and the device constants were corrected. Comparative Example 5

[0020] The heat of fusion of the untreated natural water (electrical conductivity, 28°C, approximately 60 microsiemens per centimeter (μS / cm)) used in Example 1 during the heating and melting process after freezing was measured using a differential scanning calorimeter. The results are shown in FIG. 6. 9.990 milligrams of the natural water was sealed in an aluminum sealed pan, and the natural water was frozen by cooling to minus 40°C at a temperature drop rate of 5°C per minute and holding for 1 minute. Next, the natural water was heated to 25°C at a temperature increase rate of 5°C per minute, and the heat of fusion due to the melting of the ice in the natural water during the heating process was measured using a differential scanning calorimeter. Furthermore, the natural water was again cooled to minus 40°C at a temperature drop rate of 5°C per minute and held for 1 minute to refreeze the natural water, and then heated to 25°C at a temperature increase rate of 5°C per minute, and the heat of fusion due to the remelting of the ice in the natural water during the heating process was measured again using a differential scanning calorimeter. The endothermic curves observed when the ice in the natural water was melted twice were almost completely consistent with each other, and the heat of fusion was 330 Joules per gram (J / g). In assessing the heat of fusion, the heat of fusion of ice in ultrapure water measured in a similar manner was set to 333 Joules per gram (J / g), and the instrument constant was corrected.

Claims

1. Water or natural water in which the heat of fusion of ice during the heating and melting process after freezing by magnetic processing is reduced by 10% or more when the heat of fusion is measured under the same conditions compared to before the magnetic processing.

2. The water or natural water according to claim 1, which exhibits activity in enhancing plant metabolism.

3. 3. The water or natural water according to claim 1, wherein the activity of enhancing the metabolism of living organisms persists even after 30 days or more have passed since the date of magnetic treatment.

Citation Information

Patent Citations

  • Activation method of water and device therefore

    JP1999138173A

  • Production of magnetically active purified water and its treatment device

    JP1999169860A

  • Cooling medium flow passage

    JP2005040783A

  • Fluid processing equipment

    JP3164402U